(untitled) (Global Journal of Science Frontier Research, 2015)
Typhoons Man-Yi and Krosa are analyzed. It is found that the wave characteristics are similar in both hurricane and typhoon. Relations amongst sea surface roughness, wind speed at 10m, and wave parameters are also formulated and presented for engineering applications.